2012
DOI: 10.1111/j.1600-0668.2012.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of gas cooking with children’s respiratory health: results from GINIplus and LISAplus birth cohort studies

Abstract: These analyses are consistent with the assumption of no effect of the exposure to low doses of nitrogen dioxide. The strong positive associations found between gas cooking and other indoor factors highlight the importance of considering other indoor factors when assessing health effects of gas cooking. Low-dose exposure to indoor nitrogen dioxide through gas cooking might not contribute to increase the risk of asthma and respiratory symptoms in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Presence of gas cookers in homes is an indicator of nitrogen dioxide as we saw in INMA previously [34,35] as well as a source of particles (PM 2.5 and Ultra Fine Particles) and black carbon [36]. Comparing with other longitudinal studies carried out in Europe [37,38] in this multicenter birth cohort study in Spain we found a considerable percentage of individuals exposed to gas cookers, around 45.5%. We tested for different types of gas cooking used by participants (network gas (31.6%) -primarily metane-, or bottle gas (13.9%) - primarily butane and propane in very low concentration-) and results remained stable (data not shown).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Presence of gas cookers in homes is an indicator of nitrogen dioxide as we saw in INMA previously [34,35] as well as a source of particles (PM 2.5 and Ultra Fine Particles) and black carbon [36]. Comparing with other longitudinal studies carried out in Europe [37,38] in this multicenter birth cohort study in Spain we found a considerable percentage of individuals exposed to gas cookers, around 45.5%. We tested for different types of gas cooking used by participants (network gas (31.6%) -primarily metane-, or bottle gas (13.9%) - primarily butane and propane in very low concentration-) and results remained stable (data not shown).…”
Section: Discussionsupporting
confidence: 66%
“…We evaluated exposure during pregnancy and to the best of our knowledge no other papers have been published evaluating exposure before birth, although a recent article that also found no association evaluated exposure to gas cooking at birth [38]. In our study, due to the high proportion of homes that maintain the same type of cooking range from pregnancy to the first year (91.2%) (only 3.3% changed from electric to gas and 5.5% changed from gas to electric), it is impossible to distinguish if the relationship found is related only to prenatal exposure or only to postnatal exposure or both.…”
Section: Discussionmentioning
confidence: 99%
“…However, a positive association (p<0.05) was observed between exposure to gas cooking and the exposure to other indoor factors such as dampness, tobacco smoke and pets. It was highlighted that in assessing the effects of gas cooking, the other indoor factors must be considered (55).…”
Section: Effects On Wheezing Asthma and Chronic Obstructive Pulmonarmentioning
confidence: 99%
“…Several studies6–11 reported positive associations between gas cooking and respiratory symptoms (such as wheezing, cough, nasal symptoms and atopic rhinitis) and eczema in children, while other studies showed no effects 12–15. Most studies so far were cross-sectional; prospective birth cohort studies conducted in Europe16 17 and Canada18 have also examined the associations between gas cooking exposure and childhood respiratory diseases. However, analyses within most16 18 of the previous birth cohorts have been essentially cross-sectional; little evidence has been found to support an association between gas cooking exposure and asthma.…”
Section: Introductionmentioning
confidence: 99%